(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: Herpetic stromal keratitis (HSK) is an immunomodulatory disease that develops as a result of herpes simplex virus (HSV)1 or HSV2 reactivation. HSK is the most common form (20-50%) of recurrent herpetic keratitis (HK) that most commonly results in significantly reduced vision. It is well known that changes in biological compound levels in tear fluid can be indicative of the state of the ocular surface and determine whether ocular surface pathology is present, and, therefore, can be used as diagnostic markers of pathological changes in the ocular surface. Lactoferrin (LF) is one of these compounds and has been proven to have innate antibacterial, antifungal, antiviral, antiparasite, anti-inflammatory, immunomodulatory, antioxidative and other properties. Purpose: To determine tear Lf concentration in patients with recurrent acute HSK, its effect on functional characteristics of the ocular surface, and the therapeutic effect of Lacto eyedrops in the comprehensive treatment for this disorder. Material and Methods: The study was conducted at the site of Corneal Pathology Department and Immunology Laboratory of the Institute in January to December 2021. Seventeen patients (17 affected eyes and 17 fellow eyes) with recurrent acute HSK were included in the study. Mean patient age plus or minus standard deviation (SD) was 48.7 ± 16.0 years. The ophthalmological examination included biomicroscopy of the bulbar conjunctiva and cornea, fluorescein test, determination of corneal sensation and basal tear production (Schirmer’s II test), and microbiological examination of the conjunctiva. Tear Lf concentration was determined by a human Lf enzyme-linked immunosorbent assay (ELISA) kit (Elabscience Biotechnology, Inc., Wuhan, China). The results were photometrically measured at 450 nm with an ELISA reader (Stat Fax 2100, Awareness Technology Inc, Palm City, FL). Lacto eyedrops were administered two times a day for 30 days. Tear Lf concentrations were determined at baseline and at day 30. Results: Mean tear LF concentration plus or minus SD in eyes of patients with recurrent HSK was 1.21 ± 0.52 g/l, with no significant difference between the affected eye and fellow eye. However, a subnormal tear LF concentration was more common in the affected eye than in the fellow eye (χ2 = 4.24, р = 0.04). After a 30-day anti-inflammatory treatment with Lacto eyedrops, mean tear LF concentration plus or minus SD increased by 47% to 1.78 ± 0.7 g/l in the affected eyes. A corneal sensation score of 1 to 9 was 12.4 times more common in HSK eyes than in fellow eyes (OR = 12.4; 95% CI, 2.0–76.8), which reflects neurosensory abnormalities in the affected eye. Corneal sensation loss, was, however, more common in HSK eyes with a low tear Lf concentration than in fellow eyes with a low tear Lf concentration. Median basal tear production (as assessed by Schirmer’s II test) was as low as 7-8 mm in eyes with a low tear Lf concentration and as high as 13-16 mm in eyes with a high tear Lf concentration (p < 0.05). There was a direct correlation between the basal tear production and the tear Lf concentration (r=0.45; p < 0.05). Among study patients with recurrent HSK, 24.9% showed baseline microbiological evidence of potentially pathogenic or fungal organisms in the conjunctiva. A course of multicomponent anti-inflammatory treatment with Lacto eyedrops contributed to complete removal of these organisms. Conclusion: We determined mean tear Lf concentrations in affected and fellow eyes of patients with recurrent HSK, and established certain relationships between functional characteristics of the ocular surface and tear Lf concentrations in these eyes. A disinfecting effect of Lacto eyedrops against any microorganisms present in the conjunctival sac of patients with recurrent HSK was confirmed by the absence of culture growth on completion of the multicomponent anti-inflammatory treatment.